Analisis Semiotika terhadap Pemberitaan Efisiensi Anggaran Kabinet Prabowo di Kompas TV - Roslia Arfanti; Liliana Muliastuti; Siti Ansoriyah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study examines the ideological construction of meaning in Kompas TV news reporting on the Prabowo-Gibran cabinet's budget efficiency policy. The news article, published on February 19, 2025, juxtaposes public sector cuts with substantial official uniform allocations, suggesting inherent bias. While previous research has analyzed this text using Peirce's semiotics alone, this paper adopts a multi-theoretical framework incorporating Ferdinand de Saussure, Charles Sanders Peirce, Roland Barthes, and Umberto Eco to achieve a more comprehensive critical analysis. Through qualitative semiotic analysis, the study reveals that linguistic choices such as "was-was" and "fantastis" strategically shape ideological narratives at syntagmatic and paradigmatic levels. Peirce's triadic model identifies the official uniform as an icon of bureaucratic excess, budget figures as causal indexes, and efficiency terminology as contested symbols undergoing unlimited semiosis. Barthes' denotation-connotation-myth framework exposes a hidden myth portraying officials enjoying luxury while citizens endure austerity. Eco's perspective demonstrates that the news functions as a closed text, channeling readers toward a dominant interpretation by exploiting Indonesian cultural units and collective distrust in bureaucracy. These findings affirm that news texts are not neutral but active sites of ideological meaning construction, underscoring the necessity of critical media literacy.